The effects of hormone replacement therapy on mammographic density among postmenopausal women in Hospital Raja Perempuan Zainab Ii, Kota Bharu, Kelantan. - Kamaravel, Shanti (2011)
Introduction Hormone replacement therapy (HRT) is commonly prescribed to postmenopausal women to improve their postmenopausal symptoms. Postmenopausal hormone use is associated with increase in mammographic density and increased incidence of breast pain. Mammographic density is an independent risk factor for breast cancer. Objective Our purpose was to evaluate the effects of hormone replacement therapy on mammographic density in postmenopausal women in Kota Bharu, Kelantan, Malaysia. Material and Method An observational study was conducted for a period of 18 months. A total of 33 postmenopausal women who received combined hormone replacement therapy (containing estrogen and progesterone) were included as study subjects. Mammograms were performed at baseline and after 12 months of receiving HRT. Mammographic density was evaluated according to BIRADS classification of breast density. During follow-up, patients were also enquired about breast pain and they were asked to classify according to a specified scale. Result The categorical assessments showed that there was a significant shift in categorical classification as assessed by BIRADS categories among the postmenopausal women receiving hormone replacement therapy. Amongst these women, 30.3% had increased mammographic density after treatment with HRT. There was also significant xiv association between breast pain and increase in mammographic density. Amongst the study population, 33.3% complained of breast pain after hormonal therapy. We also concluded that the study factors (grade, age, parity, BMI, duration of menopause and age at menopause) did not significantly influence change in mammographic density. Conclusion Hormone replacement therapy significantly affects the mammographic density and increased mammographic density was associated with breast pain in women receiving hormonal therapy.